Holistic Education Management in Schools, Madrasahs, and Pesantren - Gusti, Gusti; Annur, Saipul; Mohamad, Mua'azam (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines holistic education management within three major educational institutions in Indonesia: schools, madrasahs, and Islamic boarding schools (pesantren). Holistic education is understood as an integrated approach that combines academic, emotional, social, and spiritual development to promote balanced learner growth. This literature review identifies four core strategies relevant to strengthening holistic management: School-Based Management (SBM) and stakeholder participation; the integration of character and spiritual education; Total Quality Management (TQM) supported by data-driven evaluation; and the development of human resources alongside constructive conflict resolution. Sources were collected through systematic searches of academic publications from the last decade, focusing on studies discussing holistic education, educational management, and Islamic educational institutions. The findings indicate that SBM enhances autonomy, community involvement, and institutional accountability; character-spiritual integration strengthens ethical formation; TQM ensures continuous quality improvement; and competent human resource management fosters a positive school climate and sustainable organizational performance. These integrated strategies demonstrate that holistic education management is essential for improving institutional responsiveness, educational quality, and learner well-being. The study concludes that applying a holistic management framework across schools, madrasahs, and pesantren can provide an adaptive, culturally grounded, and future-oriented model for educational development in Indonesia.